Delivery of Nusinersen Through an Ommaya Reservoir in Spinal Muscular Atrophy. Issue 3 (March 2021) - Iannaccone, Susan T.; Paul, Dustin; Castro, Diana; Weprin, Bradley; Swift, Dale
Abstract: Objective: Spinal muscular atrophy (SMA) is a common rare neuromuscular disease responsible for very high mortality during infancy and high morbidity during childhood and adolescence. It is caused by autosomal recessive mutations in the survival motor neuron gene. In 2016, the Food and Drug Administration approved the first disease modifying therapy for use in all patients of any age. Nusinersen is an antisense oligonucleotide that showed dramatic benefits with achievement of motor milestones in infants and improved gross motor function in children. Methods: This was a retrospective chart review of all SMA patients seen at a single site between 2016 and 2020 for treatment with nusinersen. Results: We report 8 patients who underwent placement of an Ommaya reservoir and lumbosacral catheter for drug delivery. Complications included infection and revisions due to catheter separation. One patient required fluoroscopy for injections because of location of port site. Conclusion: We conclude that placement of an Ommaya port is a viable option for patients who have challenges for access to intrathecal space. Practical innovations have the potential to control administration costs, achieve therapeutic value, and promote patient safety.